DEPRESSIONATION OF JOKO WIDODO RUPIAH ERA: AN ARCHITECTONIS ECONOMIC POLITICS - Herabudin Herabudin (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This research has become quite important as Indonesian’s currency or known as rupiah, has reached its highest depreciation to US dollars like never before 18 years. Aim of this research is to find out whether the policy of Joko Widodo or Jokowi to increase national debt has any correlation with rupiah depreciation in a political economy perspective. In conclusion, there are at least three points. Firstly, although there is a long history of how Indonesia involve in such a capitalistic economic system, Jokowi policy itself solely is a mistake, at least according to political economy philosophy of Indonesia. Secondly, there is a positive correlation between national debt and rupiah depreciation. Moreover, the prediction has been positively predicted. This condition happened as the result of poor Indonesian economy during the first year of Joko Widodo. Thirdly, worsen of rupiah depreciation is the result of improper policy adds up with the poor condition of Indonesia.